Introduction to Satellite Oceonography. Issue 1 (2014) - Marra, John
Summary: This lecture is designed for undergraduates, to show how satellites contribute to the understanding of ocean dynamics. Satellite sensors can measure properties of the surface ocean with a sampling coverage unachievable from ocean‐going research vessels. The four geophysical variables of the ocean that satellites can observe are sea‐surface temperature, surface winds, the relative height of the sea surface, and the color of the ocean. Sea surface temperature is measured by sensing the infrared radiation emanating from the ocean. Surface winds are deduced from the roughness of the surface ocean using a radar on the satellite. Sea surface height is estimated from knowing, very accurately the altitude of the satellite relative to the earth. Ocean color is measured with a spectrometer on board the satellite. The lecture will give students appreciation of the power of satellite oceanography, while also considering its limitations. This lecture avoids overly technical information and the particulars of the various satellites, in favor of a description of how the measurements are made that can be understood at the undergraduate level. Students are encouraged to make use of satellite data, which is publicly available.